Implementation of Coaching Approach to Formation, Maintenance and Development of Safety Culture at the «Rosatom» State Corporation Enterprises - Rudenko, V. A.; Evdoshkina, Yu. A.; Vasilenko, I. S. (Глобальная ядерная безопасность, 2022)
The paper considers the possibility of using coaching as an innovative and effective technology for managerial interaction with personnel in the daily activities of the nuclear power plant leaders. The results of diagnostics of the development of management skills of managers at the Rostov nuclear power plant are presented. The obtained results of the study can be used as the basis for the strategy of forming and increasing leadership in matters of safety culture at the enterprises of the nuclear industry